2016
DOI: 10.1016/j.ejvs.2016.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Displacement Forces in Stent Grafts: Influence of Diameter Variation and Curvature Asymmetry

Abstract: Flow induced displacement forces in iliac limb stent grafts are significant and are influenced by distal stent graft diameter and the shape of the graft curvature. The displacement forces are particularly high at the large distal end of bell-bottom grafts. Wide iliac arteries treated with bell-bottom stent grafts may require more vigilant surveillance and improved stent graft fixation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…The force applied on the flared iliac limb and the hemodynamic pattern is not the same as in a straight limb which can influence the outcome presented in an experimental study. 21 Limb graft oversizing can induce or accelerate iliac vessel degeneration as described in a report as well. 17 Technical success and immediate results are good in the present study but the occurrence of the type Ib endoleak is to be expected in a mid-and long-term follow-up period.…”
Section: Discussionmentioning
confidence: 83%
“…The force applied on the flared iliac limb and the hemodynamic pattern is not the same as in a straight limb which can influence the outcome presented in an experimental study. 21 Limb graft oversizing can induce or accelerate iliac vessel degeneration as described in a report as well. 17 Technical success and immediate results are good in the present study but the occurrence of the type Ib endoleak is to be expected in a mid-and long-term follow-up period.…”
Section: Discussionmentioning
confidence: 83%
“…Our results also showed that the displacement force would increase as the taper degree increased, when considering the taper feature. Roos et al also investigated the effects of perfusion pressure and the taper feature on displacement force through in vitro experiments [ 32 ]. The displacement force waveforms were seen to have similar temporal behavior to those of the perfusion pressure waveform.…”
Section: Discussionmentioning
confidence: 99%
“…Roos et al . [4] discussed the complex factors influencing migration of stents. They indicated that the distal displacement forces are significantly increased in the bell-bottom-shaped stent.…”
Section: Discussionmentioning
confidence: 99%